The specific secondary biological activities of rabbit IgM and IgG anti-Salmonella typhimurium `O' antibodies isolated during the development of the immune response - Schulkind, M. L. (1972)
Purified IgM and IgG anti-Salmonella typhimurium `O' antibodies were isolated at various intervals during the primary and secondary immune responses. Using agglutination, complement-dependent bactericidal effect and passive inhibition of antibody formation assays, the specific activities of IgM antibodies were found to be higher than IgG antibodies isolated at the same interval. As the immune response developed, a progressive increase in the specific secondary biological activities of both immunoglobulins was detected. In selected experiments, antibodies of a single immunoglobulin class were further fractionated into populations of molecules of different activity. An indirect assay of `avidity' indicated that there was a direct relationship between this measure of antigen—antibody interaction and the secondary biological properties of these immunoglobulins.